2020
DOI: 10.3390/genes11101156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light Intensity on the Expression of Leucoanthocyanidin Reductase in Grapevine Calluses and Analysis of Its Promoter Activity

Abstract: To investigate the effect of light intensity on flavonoid biosynthesis, grapevine calluses were subjected to high light (HL, 250 μmol m−2 s−1) and dark (0 μmol m−2 s−1) in comparison to 125 μmol m−2 s−1 under controlled conditions (NL). The alteration of flavonoid profiles was determined and was integrated with RNA sequencing (RNA-seq)-based transcriptional changes of the flavonoid pathway genes. Results revealed that dark conditions inhibited flavonoid biosynthesis. Increasing light intensity affected flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Recently, by calculating the correlations between the expression levels of structural and regulatory genes in the PA biosynthesis branch of grapevine calluses subjected to different light intensities, researchers showed that VviLAR2 was the target gene of VviMYBPA2. However, owing to the low expression level of VviMYBPA2 , the effects on the expression level of VviLAR2 are limited ( Cheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, by calculating the correlations between the expression levels of structural and regulatory genes in the PA biosynthesis branch of grapevine calluses subjected to different light intensities, researchers showed that VviLAR2 was the target gene of VviMYBPA2. However, owing to the low expression level of VviMYBPA2 , the effects on the expression level of VviLAR2 are limited ( Cheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies show that the promoter of VviLAR1 contains multiple E/G box elements, which are supposed to be the motifs for bHLH transcription factor recognition (Cheng et al, 2020(Cheng et al, , 2021. However, bHLH proteins that directly regulate VviLAR1 remain unknown.…”
Section: Identification Of Vvibhlh93mentioning
confidence: 99%
“…The expression of VviLAR1 is restricted in flowers, young berries, and seeds, while VviLAR2 transcript is mainly detected in berry skins before veraison, seeds during veraison, and expending leaves (Bogs et al, 2005). In addition, previous studies show that the expression of VviLAR1 and VviANR is light-inducible, whereas the promoter activity of VviLAR2 is not sensitive to the change of light intensity (Koyama et al, 2012;Sun et al, , 2019Cheng et al, 2020). The above findings imply that different regulation mechanisms are underlying the expression of the three PA-specific genes in grapevine.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tissue culture technology, one of the technologies of plant production, enables the differentiation of cells into tissues or organs by the totipotency of plants, therefore it is at the center of researches into plant systems capable of producing specific metabolic products. Through cells and callus suspension culture, it has the advantages of genetic and biochemical stability, hormone autotrophy, and multienzyme biosynthetic capacity, etc., as a biocatalyst [ 47 , 48 ]. The synthesis of metabolites and biotransformation by an “elicitor” can bring about changes in subjects for research in substances originating from plants, which are realistically unavailable.…”
Section: Introductionmentioning
confidence: 99%